Collaborative Governance Effort to Manage Forest in Kalimantan Island: Literature Review - Cahyoko Edi Tando; Sudarmo; Rina Herlina Haryanti (Jurnal Manajemen Hutan Tropika, 2022)
Deforestation has given many problems to all the survival of living things throughout the world. Becoming one of the main issues in Kalimantan Island, there is a need for deforestation prevention and land restoration that must be carried out by all stakeholders including government, private sector, and the local community. Collaborative governance is expected to be a solution to deforestation in Kalimantan. The purpose of this research is to map out several collaborative governance efforts in forest management with local communities in Kalimantan. This research uses systematic literature review (SLR) approach on finding relevant articles for answering the formulated problems. The results of this study are the discovery of two main points in forest management efforts through collaborative governance with local communities: 1) collaboration between village communities (community forest) and state forest companies, called collaborative forest management programs (CFMP) and 2) social learning.